2017
DOI: 10.18203/2320-6012.ijrms20173550
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia during pregnancy: an institutional based prospective study of one year

Abstract: Background: Platelets are non-nucleated cellular fragments of megakaryocytes, they play a critical role in haemostasis. Thrombocytopenia, defined as blood platelet count below 150.000/μL is the second leading cause of blood disorders in pregnancy after anemia. It complicates 7 to 10% of all pregnancies. Gestational thrombocytopenia explains 70-80% of all cases of thrombocytopenia in pregnancy. Hypertensive disorders account for approximately 20% and immune thrombocytopenic purpura for about 3-4%. Other etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Pregnancy triggers various biological mechanisms that affect hematopoietic and related systems [1]. Thrombocytopenia is the second most common hematologic disorder after anemia [2]. The incidence of thrombocytopenia during pregnancy has been shown to be between 6 and 10 % and is defined as a platelet count < 150 × 10 3 /µl [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy triggers various biological mechanisms that affect hematopoietic and related systems [1]. Thrombocytopenia is the second most common hematologic disorder after anemia [2]. The incidence of thrombocytopenia during pregnancy has been shown to be between 6 and 10 % and is defined as a platelet count < 150 × 10 3 /µl [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, severe thrombocytopenia was seen in 6.73% of pregnant women which is almost similar to the study conducted by Singh et al [17] (7.4%), Vishwekar et al [18] (6.4%) and Zutshi et al [16] (7%). Severe thrombocytopenia was seen in higher percentage of pregnant women (20%) in the study by Pandey et al [19] However, Chauhan et al [11] observed a very low (1.5%) incidence of severe thrombocytopenia the reason of which was not explained by them. [17] 74.7% 17.9% 7.4% Vishwekar et al [18] 78.4% 15.2% 6.4% Chauhan et al [11] 63.1% 35.4% 1.5% Zutshi et al [16] 62% 31% 7% Pandey et al [19] 22% In our study, gestational thrombocytopenia (69.23%) was the commonest etiology which was similar to the study conducted by Vishwekar et al [18] (68.46%) and Chauhan et al [11] (68.2%).…”
Section: Discussionmentioning
confidence: 90%
“…Severe thrombocytopenia was seen in higher percentage of pregnant women (20%) in the study by Pandey et al [19] However, Chauhan et al [11] observed a very low (1.5%) incidence of severe thrombocytopenia the reason of which was not explained by them. [17] 74.7% 17.9% 7.4% Vishwekar et al [18] 78.4% 15.2% 6.4% Chauhan et al [11] 63.1% 35.4% 1.5% Zutshi et al [16] 62% 31% 7% Pandey et al [19] 22% In our study, gestational thrombocytopenia (69.23%) was the commonest etiology which was similar to the study conducted by Vishwekar et al [18] (68.46%) and Chauhan et al [11] (68.2%). The incidence of thrombocytopenia in neonates born to gestational thrombocytopenic women is similar to those reported ~ 131 ~ in non gestational thrombocytopenia women [20] .…”
Section: Discussionmentioning
confidence: 90%
“…9 According to Sibai, the rate of cesarean section with HELLP syndrome is significant, especially when the pregnancy is shorter than 34 weeks. 10 The cesarean section rate in pregnancies fewer than 30 weeks is 87.0%. 11 Maternal complications due to bleeding tendencies like placental abruption, postpartum haemorrhage were not evident in the study population, only 2 cases of DIC and 6 cases of ICU admission noted as maternal complication.…”
Section: Discussionmentioning
confidence: 99%